Facile hydrothermal synthesis of urchin‐like NiCo2O4 as advanced electrochemical pseudocapacitor materials - Yan, Sheng‐xue; Luo, Shao‐hua; Sun, Mei‐zhu; Wang, Qing; Zhang, Ya‐hui; Liu, Xin (International journal of energy research, 2021)
Summary The urchin‐like NiCo2O4 material was prepared by a one‐step hydrothermal method. The optimal synthetic conditions were systematically investigated by an orthogonal test method and single factor of hydrothermal time to evaluate the influence of sample morphology and electrochemical performance. The synthesis conditions for preparing NiCo2O4 with different morphologies were systematically studied. In the single factor experiment, when the hydrothermal time is 6, 12, 16, and 24 hours, the corresponding morphologies are urchin‐like (NCO‐U), flower‐like (NCO‐F), sheet‐like (NCO‐S), and block‐like (NCO‐B), respectively. The element content of the prepared materials under different synthesis conditions was tested by an inductive‐coupled plasma emission spectrometer, and an interesting phenomenon was found. As the reaction time increases, the content of Ni+ gradually decreases and the content of Co+ gradually increases, which may be one of the factors that affect the morphology and electrochemical performance of the material. The specific capacitances of NCO‐U, NCO‐F, NCO‐S, and NCO‐B are calculated to be 914.3, 392.2, 313.3, and 277.4 F g−1, respectively, at a current density of 1 A g−1. Benefiting from the large specific surface area and rich oxygen vacancy, the as‐fabricated urchin‐like NiCo2O4 as electrode materials for supercapacitor demonstrates its promising application potential for supercapacitors. This study reports the influence of the hydrolyzing agent urea on the structure and electrochemical performance of the urchin‐like NiCo2O4 nanostructured electrode for the next generation of supercapacitors.